Functional Levels and Influencing Factors of Patients with Chronic Pain in the Neck，Shoulders，Waist and Legs Based on the International Classification of Functioning，Disability and Health Rehabilitation Set - SUN Qianqian; ZHANG Chao; LI Rui; ZHANG Luwen; ZHANG Shuqin; XIONG Tianyi; LIU Chang; XIE Hongwu (康复学报)
ObjectiveThis study explores the use of the International Classification of Functioning, Disability and Health Rehabilitation Set (ICF-RS) to evaluate the physical, activities, and social participation levels of patients with chronic neck, shoulder, waist, and leg pain, and to explore its influencing factors.MethodsA total 162 patients with chronic neck, shoulder, hip and leg pain from the outpatient departments of the Central Hospital of Xiangyang City from July to December 2023, who had meet the diagnostic criteria and inclusion and exclusion criteria for chronic pain. A trained assessor used a questionnaire to collect detailed information on the patients' basic demographic data (sex, age, education level, medical expenses, body mass index), lifestyle habits (smoking, drinking), medical history (hypertension, hyperlipidemia, diabetes), and use of pain medication. The patients were assessed for their functional levels (physical function, activity function, social participation) using the ICF-RS. A multivariate ordered Logistic regression analysis was used to identify independent risk factors for the patients' body function, activity function, and social participation function (mild, moderate, and severe impairment).ResultsAmong the three dimensions of physical function, daily activities, and social participation of patients with chronic pain in outpatient clinics, about 1/3 of them with mild functional impairments being the main type. There were 10 ICF-RS categories (33.33%) with a functional impairment proportion > 50%, involving 4 categories in the physical function dimension, 2 categories in the daily activity function dimension, and 4 categories in the social participation dimension. The differences in exercise tolerance and mobility function among patients with chronic pain of different age groups were statistically significant (P=0.040, P=0.030); the differences in the ability to help others among patients with chronic pain of different age groups and whether they drank alcohol were statistically significant (P=0.008, P=0.021); the differences in entertainment and leisure ability among patients with chronic pain of different age groups and whether they had hyperlipidemia were statistically significant (P=0.028, P=0.004).ConclusionPatients with chronic pain have varying degrees of functional impairments in their body function, daily activities function, and social participation function, with mild functional impairments being the predominant; Age, alcohol consumption, and hyperlipidemia are independent influencing factors for functional impairment in body function, daily activity function, and social participation function.